Synthesis and characterization of silver-doped zinc oxide nanorods on titanium dioxide seeded substrate: potential application as UV sensor / Siti Zulaikha Umbaidilah - Umbaidilah, Siti Zulaikha (2021)
Zinc Oxide (ZnO)-based UV Sensor has been investigated widely and it is realized that the performance of this device depends on the dimension, morphology and the structure of ZnO. One of the efforts that lead to the surface modification of ZnO is by introducing dopant in ZnO which is expected to improve certain properties of ZnO and hence enhancing the performance of UV Sensor. In this work, metal-doped ZnO were grown on titanium dioxide (TiO2) seed layer by using a spin-coating technique for the deposition of TiO2 seed layer and the solution-immersion method for the growth of metal-doped ZnO. The effectiveness of TiO2 as a seed layer was investigated and it proved that the presence of TiO2 as a seed layer revealed a smaller diameter size of nanorods (392nm) with high absorption properties of ZnO compared with pure ZnO (1226nm). Then, the preparation towards the optimization of metal-doped ZnO nanorods on TiO2 seed layer was also studied.